Combined Plasma Elevation of CRP, Intestinal-Type Fatty Acid-Binding Protein (I-FABP), and sCD14 Identify Older Patients at High Risk for Health Care-Associated Infections. (3rd June 2017) - Paillaud, Elena; Bastuji-Garin, Sylvie; Plonquet, Anne; Foucat, Emile; Fournier, Bénédicte; Boutin, Emmanuelle; Le Thuaut, Aurélie; Levy, Yves; Hue, Sophie
Abstract: Background: We hypothesized that low-grade inflammation was driven by microbial translocation and associated with an increased risk of health care-associated infections (HAIs). Methods: We included 121 patients aged 75 years or over in this prospective cohort study. High-sensitivity C-reactive protein (hs-CRP), I-FABP, and sCD14—as markers for low-grade inflammation, intestinal epithelial barrier integrity, and monocyte activation, respectively—were measured at admission. Results: HAIs occurred during hospitalization in 62 (51%) patients. Elevated hs-CRP (≥6.02 mg/L, ie, the median) was associated with a significantly higher HAI risk when I-FABP was in the highest quartile (odds ratio [OR], 4; 95% confidence interval [95% CI], 1.39–11.49; p = .010). In patients with hs-CRP elevation and highest-quartile I-FABP, sCD14 elevation (≥0.65 µg/mL, ie, the median) was associated with an 11-fold higher HAI risk (OR, 10.8; 95% CI, 2.28–51.1; p = .003). Multivariate analyses adjusted for invasive procedures and comorbidities did not change the associations linking the three markers to the HAI risk. Conclusion: Increased levels of hs-CRP, I-FABP, and sCD14 may reflect loss of intestinal epithelial barrier integrity with microbial translocation leading to monocyte activation and low-grade inflammation. In our cohort, these markers identified patients at high risk for HAIs.